Consumption of tetracyclines, sulphonamides and trimethoprim, and other antibacterials in the community, European Union/European Economic Area, 1997–2017. (1st August 2021) - Versporten, Ann; Bruyndonckx, Robin; Adriaenssens, Niels; Hens, Niel; Monnet, Dominique L; Molenberghs, Geert; Goossens, Herman; Weist, Klaus; Coenen, Samuel; ,
Abstract: Objectives: Data on consumption of tetracyclines, sulphonamides and trimethoprim, and other antibacterials were collected from 30 EU/European Economic Area (EEA) countries over two decades. This article reviews temporal trends, seasonal variation, presence of change-points and changes in the composition of main subgroups of tetracyclines, sulphonamides and trimethoprim and other antibacterials. Methods: For the period 1997–2017, data on consumption of tetracyclines (ATC group J01A), sulphonamides and trimethoprim (ATC group J01E), and other antibacterials (ATC group J01X) in the community and aggregated at the level of the active substance, were collected using the WHO ATC/DDD methodology (ATC/DDD index 2019). Consumption was expressed in DDD per 1000 inhabitants per day and in packages per 1000 inhabitants per day. Consumption of tetracyclines, sulphonamides and trimethoprim, and other antibacterials was analysed based on ATC-4 subgroups and presented as trends, seasonal variation, presence of change-points and compositional changes. Results: In 2017, consumption of tetracyclines, sulphonamides and trimethoprim, and other antibacterials in the community expressed in DDD per 1000 inhabitants per day varied considerably between countries. Between 1997 and 2017, consumption of tetracyclines did not change significantly, while its seasonal variation significantly decreased over time. Consumption of sulphonamides and trimethoprim significantly decreased until 2006, and its seasonal variation significantly decreased over time. The consumption of other antibacterials showed no significant change over time or in seasonal variation. Conclusions: Consumption and composition of tetracyclines, sulphonamides and trimethoprim, and other antibacterials showed wide variations between EU/EEA countries and over time. This represents an opportunity to further reduce consumption of these groups in some countries and improve the quality of their prescription.